The addition of adjuvants on glyphosate enhances the control of aquatic plant myriophyllum aquaticum (Vell.) - Cerveira, Wilson R. [UNESP]; Silva, Adilson F. [UNESP]; Cervoni, João H.C.; Cruz, Claudinei; Pitelli, Robinson A. (FapUNIFESP (SciELO), 2020)
Background: Knowledge about the action of glyphosate alone and associated with adjuvants in the effectiveness to control aquatic plants is important in the decision-making on its use. Objective: This study aimed to evaluate the effectiveness of glyphosate and five adjuvants in the control of Myriophyllum aquaticum. Methods: Glyphosate (Rodeo®) at doses of 1.5, 3.5, 5.5, and 7.5 L ha-1 was sprayed alone and associated with Aterbane® BR, Veget’oil®, Dash® HC, Assist®, and Agral® (0.5% v v-1), in addition to the control, with a spray solution volume of 200 L ha-1. The effectiveness of control was evaluated using the scores of a visual scale at 3, 7, 15, 21, 30, 45, and 60 days after application (DAA), regrowth, and dry matter accumulation at 60 DAA. Results: The best effectiveness of control of the glyphosate alone was 85% at the dose of 7.5 L ha-1, increasing to 100% when associated with Aterbane® and Veget’oil®. The control reached 100% for all glyphosate doses associated with Dash®. Moreover, glyphosate at the dose of 7.5 L ha-1 associated with Assist® provided a 98% control, while glyphosate doses of 3.5, 5.5, and 7.5 L ha-1 associated with Agral® provided a 100% control. Glyphosate at doses of 5.5 and 7.5 L ha-1 associated with Dash® and Agral® was more effective in reducing the regrowth and dry biomass (100%). Thus, glyphosate + Dash® and Agral® promoted the highest control (above 95%), the lowest regrowth, and the highest reduction in the dry biomass of M. aquaticum. Conclusions: The addition of Aterbane® BR, Dash®, and Agral® to glyphosate improved the effectiveness of control of M. aquaticum and contributed to reducing the applied herbicide dose.
Keywords: Aquatic plants; Chemical management; Parrot feather watermilfoil